2018
DOI: 10.21825/vdt.v87i3.16079
|View full text |Cite
|
Sign up to set email alerts
|

Perceptie, drijfveren en hindernissen van bioveiligheid in de rundveeproductie

Abstract: Farm biosecurity includes the prevention of disease transmission within and between farms. Two studies were set up to investigate what motivates and withholds farmers to implement biosecurity measures. The first study aimed to assess the perception of cattle farmers towards biosecurity and to identify possible reasons for its low application. This study consisted of a focus group discussion, of which the trends were used to develop a questionnaire for Flemish cattle farmers. Although the 91 participating farme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 54 publications
2
16
0
2
Order By: Relevance
“…Most farmers in this study were willing to invest money and time to solve shortcomings on their farm, which is in agreement with previous findings (Damiaans et al, 2018). However, farmers are often hindered by their beliefs that many biosecurity measures are not feasible or important.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Most farmers in this study were willing to invest money and time to solve shortcomings on their farm, which is in agreement with previous findings (Damiaans et al, 2018). However, farmers are often hindered by their beliefs that many biosecurity measures are not feasible or important.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, a number of the farmers considered several measures to be unimportant or impossible to implement. This finding confirms previous observations that there is a substantial lack of information on how to improve farm management and how to implement these improvements (Damiaans et al, 2018). The finding also shows that the results of previous studies that suggested measures like risk classification, limitation of the arrival period, and the farms of origin have not been translated into practice (Pardon, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations